# 5.7.1: Variation of Parameters (Exercises)

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$ $$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$$$\newcommand{\AA}{\unicode[.8,0]{x212B}}$$

## Q5.7.1

In Exercises 5.7.1–5.7.6 use variation of parameters to find a particular solution.

1. $$y''+9y=\tan 3x$$

2. $$y''+4y=\sin 2x\sec^2 2x$$

3. $$y''-3y'+2y={4\over 1+e^{-x}}$$

4. $$y''-2y'+2y=3e^x \sec x$$

5. $$y''-2y'+y=14x^{3/2}e^x$$

6. $$y''-y={4e^{-x}\over 1-e^{-2x}}$$

## Q5.7.2

In Exercises 5.7.7-5.7.29 use variation of parameters to find a particular solution, given the solutions $$y_{1}, y_{2}$$ of the complementary equation.

7. $$x^2y''+xy'- y=2x^2+2; \quad y_1=x, \quad y_2={1\over x}$$

8. $${xy''+(2-2x)y'+(x-2)y=e^{2x}; \quad y_1=e^x, \quad y_2={e^x\over x}}$$

9. $$4x^2y''+(4x-8x^2)y'+(4x^2-4x-1)y=4x^{1/2}e^x, \quad x > 0$$; $$y_1=x^{1/2} e^x,\; y_2=x^{-1/2}e^x$$

10. $$y''+4xy'+(4x^2+2)y=4e^{-x(x+2)};\quad y_1=e^{-x^2}, \quad y_2=xe^{-x^2}$$

11. $$x^2y''-4xy'+6y=x^{5/2},\, x > 0;\quad y_1=x^2,\; y_2=x^3$$

12. $$x^2y''-3xy'+3y=2x^4\sin x; \quad y_1=x,\; y_2=x^3$$

13. $$(2x+1)y''-2y'-(2x+3)y=(2x+1)^2e^{-x}; \quad y_1=e^{-x}, \quad y_2=xe^x$$

14. $$4xy''+2y'+y=\sin\sqrt x; \quad y_1=\cos\sqrt x, \quad y_2=\sin\sqrt x$$

15. $$xy''-(2x+2)y'+(x+2)y=6x^3e^x;\quad y_1=e^x,\quad y_2=x^3e^x$$

16. $$x^2y''-(2a-1)xy'+a^2y=x^{a+1}; \quad y_1=x^a, \quad y_2=x^a \ln x$$

17. $$x^2y''-2xy'+(x^2+2)y=x^3\cos x; \quad y_1=x\cos x, \quad y_2=x\sin x$$

18. $$xy''-y'-4x^3y=8x^5;\quad y_1=e^{x^2},\; y_2=e^{-x^2}$$

19. $$(\sin x)y''+(2\sin x-\cos x)y'+(\sin x-\cos x)y=e^{-x}; \quad y_1=e^{-x},\quad y_2=e^{-x}\cos x$$

20. $$4x^2y''-4xy'+(3-16x^2)y=8x^{5/2}; \quad y_1=\sqrt xe^{2x},\; y_2=\sqrt xe^{-2x}$$

21. $$4x^2y''-4xy'+(4x^2+3)y=x^{7/2}; \quad y_1=\sqrt x\sin x,\; y_2=\sqrt x\cos x$$

22. $$x^2y''-2xy'-(x^2-2)y=3x^4;\quad y_1=xe^x,\; y_2=xe^{-x}$$

23. $$x^2y''-2x(x+1)y' +(x^2+2x+2)y=x^3e^x; \quad y_1=xe^x, \quad y_2=x^2e^x$$

24. $$x^2y''-xy'-3y=x^{3/2}; \quad y_1=1/x, \quad y_2=x^3$$

25. $$x^2y''-x(x+4)y'+2(x+3)y=x^4e^x; \quad y_1=x^2, \quad y_2=x^2e^x$$

26. $$x^2y''-2x(x+2)y'+(x^2+4x+6)y=2xe^x; \quad y_1=x^2e^x, \quad y_2=x^3e^x$$

27. $$x^2y''-4xy'+(x^2+6)y=x^4; \quad y_1=x^2\cos x, \quad y_2=x^2\sin x$$

28. $$(x-1)y''-xy'+y=2(x-1)^2e^x; \quad y_1=x, \quad y_2=e^x$$

29. $$4x^2y''-4x(x+1)y'+(2x+3)y=x^{5/2}e^x; \quad y_1=\sqrt x, \quad y_2=\sqrt xe^x$$

## Q5.7.3

In Exercises 5.7.30–5.7.32 use variation of parameters to solve the initial value problem, given $$y_{1}$$, $$y_{2}$$ are solutions of the complementary equation.

30. $$(3x-1)y''-(3x+2)y'-(6x-8)y=(3x-1)^2e^{2x}, \quad y(0)=1,\; y'(0)=2$$; $$y_1=e^{2x},\; y_2=xe^{-x}$$

31. $$(x-1)^2y''-2(x-1)y'+2y=(x-1)^2, \quad y(0)=3,\quad y'(0)=-6$$;

$$y_1=x-1$$, $$y_2=x^2-1$$

32. $$(x-1)^2y''-(x^2-1)y'+(x+1)y=(x-1)^3e^x, \quad y(0)=4,\quad y'(0)=-6$$;

$$y_1=(x-1)e^x,\quad y_2=x-1$$

## Q5.7.4

In Exercises 5.7.33-5.7.35 use variation of parameters to solve the initial value problem and graph the solution, given that $$y_{1}$$, $$y_{2}$$ are solutions of the complementary equation.

33. $${(x^2-1)y''+4xy'+2y=2x, \quad y(0)=0,\; y'(0) =-2; \quad y_1={1\over x-1},\; y_2={1\over x+1}}$$

34. $${x^2y''+2xy'-2y=-2x^2, \quad y(1)=1,\; y'(1)= -1; \quad y_1=x,\; y_2={1\over x^2}}$$

35. $$(x+1)(2x+3)y''+2(x+2)y'-2y=(2x+3)^2, \quad y(0)=0,\quad y'(0)=0$$; $$y_1=x+2,\quad y_2={1\over x+1}$$

## Q5.7.5

36. Suppose

$y_p=\overline y+a_1y_1+a_2y_2$

is a particular solution of

$P_0(x)y''+P_1(x)y'+P_2(x)y=F(x), \tag{A}$

where $$y_1$$ and $$y_2$$ are solutions of the complementary equation

$P_0(x)y''+P_1(x)y'+P_2(x)y=0.$

Show that $$\overline y$$ is also a solution of (A).

37. Suppose $$p$$, $$q$$, and $$f$$ are continuous on $$(a,b)$$ and let $$x_0$$ be in $$(a,b)$$. Let $$y_1$$ and $$y_2$$ be the solutions of

$y''+p(x)y'+q(x)y=0$

such that

$y_1(x_0)=1, \quad y_1'(x_0)=0, \quad y_2(x_0)=0, \quad y_2'(x_0)=1.$

Use variation of parameters to show that the solution of the initial value problem

$y''+p(x)y'+q(x)y=f(x), \quad y(x_0)=k_0,\; y'(x_0)=k_1,$

is

$\begin{array}{rcl} y(x) &= k_0y_1(x)+k_1y_2(x) \\ & +\int^x_{x_0}\left(y_1(t)y_2(x)- y_1(x)y_2(t)\right) f(t)\exp\left(\int^t_{x_0}p(s)\,ds\right)\,dt. \end{array}$

HINT: Use Abel's formula for the Wronskian of $$\{ y_{1}, y_{2}\}$$, and integrate $$u_{1}'$$ and $$u_{2}'$$ from $$x_{0}$$ to $$x$$.

Show also that

$\begin{array}{rcl} y'(x) &= k_0y_1'(x)+k_1y_2'(x) \\ & +\int^x_{x_0}\left(y_1(t)y_2'(x)-y_1'(x)y_2(t) \right)f(t)\exp\left(\int^t_{x_0}p(s)\,ds\right)\,dt. \end{array}$

38. Suppose $$f$$ is continuous on an open interval that contains $$x_0=0$$. Use variation of parameters to find a formula for the solution of the initial value problem

$y''-y=f(x), \quad y(0)=k_0,\quad y'(0)=k_1.$

39. Suppose $$f$$ is continuous on $$(a,\infty)$$, where $$a<0$$, so $$x_0=0$$ is in $$(a,\infty)$$.

1. Use variation of parameters to find a formula for the solution of the initial value problem $y''+y=f(x), \quad y(0)=k_0,\quad y'(0)=k_1.$ HINT: You will need the addition formulas for the sine and cosine. \begin{aligned} \sin (A+B)&=\sin A\cos B +\cos A\sin B \\ \cos (A+B) &=\cos A\cos B - \sin A\sin B \end{aligned} For the rest of this exercise assume that the improper integral $$\int_{0}^\infty f(t)\,dt$$ is absolutely convergent.
2. Show that if $$y$$ is a solution of $y''+y=f(x) \tag{A}$ on $$(a,\infty)$$, then $\lim_{x \to \infty}\left(y(x)-A_0\cos x-A_1\sin x\right)=0 \tag{B}$ and $\lim_{x\to\infty}\left(y'(x)+A_0\sin x-A_1\cos x\right)=0, \tag{C}$ where $A_0=k_0-\int_0^\infty f(t)\sin t\,dt \quad \text{and} \quad A_1=k_1+\int_0^\infty f(t)\cos t\,dt.$ HINT: Recall from calculus that if $$\int _{0}^{\infty} f(t)dt$$ converges absolutely, then $$\lim_{x\to ∞}\int_{x}^{\infty}|f(t)|dt=0$$.
3. Show that if $$A_0$$ and $$A_1$$ are arbitrary constants, then there’s a unique solution of $$y''+y=f(x)$$ on $$(a,\infty)$$ that satisfies (B) and (C).

This page titled 5.7.1: Variation of Parameters (Exercises) is shared under a CC BY-NC-SA 3.0 license and was authored, remixed, and/or curated by William F. Trench.